2019
DOI: 10.1186/s12879-019-4044-x
|View full text |Cite
|
Sign up to set email alerts
|

Demographic characteristics of transfusion-transmitted infections among blood donors in China

Abstract: Background Demographic characteristic surveillance of transfusion-transmitted infections (TTIs) among blood donors is crucial to formulating control strategies and preventing TTIs. This study aimed to investigate the demographic characteristics and social factors associated with TTIs among blood donors from 14 different blood centers or banks in China, covering almost the entire China. Methods Demographic information of 1976 blood donations were obtained from the donor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
10
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 15 publications
5
10
1
1
Order By: Relevance
“…Furthermore, this study found that the seroprevalence of TTIs decreased with an increase in the education level [9]. These results are in accordance with the findings from other countries including Ethiopia, China, and Turkey [11][12][13]. Another study reported that the seroprevalence of HTLV1 was higher in female, married, and older blood donors [8].…”
Section: Introductionsupporting
confidence: 90%
“…Furthermore, this study found that the seroprevalence of TTIs decreased with an increase in the education level [9]. These results are in accordance with the findings from other countries including Ethiopia, China, and Turkey [11][12][13]. Another study reported that the seroprevalence of HTLV1 was higher in female, married, and older blood donors [8].…”
Section: Introductionsupporting
confidence: 90%
“…Transfusion Transmitted Infections (TTI) especially hepatitis B virus (HBV), hepatitis C virus (HCV), human immunodeficiency virus (HIV) always pose threat to blood transfusion services. 1 National AIDS Control major concern as it is responsible for significant global morbidity and mortality with an estimated more than half a million deaths across the world. 6 It has been shown that ABO blood groups have some connections with a variety of infectious and non-infectious diseases along with susceptibility to some infections.…”
Section: Introductionmentioning
confidence: 99%
“…Between November 2012 and December 2017, 682 specimens from voluntary blood donors tested positive for anti-HCV were collected in 22 blood centers/banks from 17 provinces and municipalities including Beijing, Chongqing, Gansu, Hebei, Heilongjiang, Henan, Hubei, Hunan, Inner Mongolia, Jiangsu, Jilin, Liaoning, Ningxia, Shaanxi, Shandong, Shenzhen and Tianjin. These specimens were primary screened with EIA assays mentioned previously [ 20 ] and then transported on dry ice to National Center for Clinical Laboratories (NCCL) in Beijing. Figure 1 demonstrated the flow chart representing the study process.…”
Section: Methodsmentioning
confidence: 99%